2016
DOI: 10.12705/663.5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and systematics of African Melastomateae (Melastomataceae)

Abstract: Melastomateae are the most species-rich (185 spp./13 gen.) and morphologically diverse tribe within the African Melastomataceae. In this study we present the first in-depth phylogenetic analysis of African Melastomateae using sequences generated from one nuclear (nrITS) and two plastid spacers (accD-psaI, psbK-psbL) sampling 183 accessions representing 75 African, 10 Madagascan and 7 Asian species and a broad outgroup sampling. We infer phylogenetic relationships using maximum likelihood, maximum parsimony and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
3
48
0
Order By: Relevance
“…However, if this topology holds with increased sampling of taxa and genetic loci, it would suggest that the mostly Asian Sonerileae-Dissochaeteae complex originated in South America and then dispersed to Africa and later to Asia where it diversified. A similar pattern has been found to the Melastomateae (Michelangeli et al 2013, Veranso-Libalah et al 2017. Recent phylogenetic studies of the Sonerileae-Dissochaeteae complex have already shown that most genera are not monophyletic and the group needs considerable further study (Zeng et al 2016, Zhou et al 2019a, 2019b.…”
Section: Discussionsupporting
confidence: 73%
“…However, if this topology holds with increased sampling of taxa and genetic loci, it would suggest that the mostly Asian Sonerileae-Dissochaeteae complex originated in South America and then dispersed to Africa and later to Asia where it diversified. A similar pattern has been found to the Melastomateae (Michelangeli et al 2013, Veranso-Libalah et al 2017. Recent phylogenetic studies of the Sonerileae-Dissochaeteae complex have already shown that most genera are not monophyletic and the group needs considerable further study (Zeng et al 2016, Zhou et al 2019a, 2019b.…”
Section: Discussionsupporting
confidence: 73%
“…Notes -This uncommon species was first described as Heterotis arenaria by Jacques-Félix (1988) from a single specimen collected in the extreme south of Gabon, and later as H. obamae by Lejoly & Lisowski (1999) from Equatorial Guinea. Parmentier & Geerinck (2003) recognised the two species as identical, an observation overlooked by subsequent authors (Sosef et al 2006, Harris et al 2012, Veranso-Libalah et al 2017. The species is now recorded from six localities along the coast of southern Gabon, and two in Equatorial Guinea.…”
Section: Thaumatococcus Flavus Acley Figs 8h-j and 9amentioning
confidence: 91%
“…Molecular phylogenetic analyses have proven useful in resolving relationships at the generic level in Melastomataceae (Ionta et al, 2007;Reginato et al, 2010;Stone & Andreasen, 2010;Stone, 2014;Kriebel, 2016;Reginato & Michelangeli, 2016;Veranso-Libalah et al, 2017). Several phylogenetic studies had included Phyllagathis or Phyllagathis and Bredia in their analyses (Clausing et al, 2000;Clausing & Renner, 2001b;Fritsch et al, 2004;Zeng et al, 2016aZeng et al, , 2016bZhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%